A novel PEG–haloperidol conjugate with a non-degradable linker shows the feasibility of using polymer–drug conjugates in a non-prodrug fashion. Issue 47 (15th November 2016) - Heath, Felicity; Newman, Amy; Clementi, Chiara; Pasut, Gianfranco; Lin, Hong; Stephens, Gary J.; Whalley, Benjamin J.; Osborn, Helen M. I.; Greco, Francesca
Abstract : A PEG–haloperidol conjugate was synthesised, which retains binding to the dopamine D2 receptor, showing the possibility of using polymer-drug conjugates as drugs per se ' rather than as prodrugs. Abstract : A PEG–haloperidol conjugate containing a non-biodegradable linker was synthesised. Incubation with rat plasma demonstrated excellent linker stability, and competition radioligand binding assays demonstrated retained binding to the D2 -receptor. In silico studies predicted that the conjugate will not cross the blood–brain barrier (BBB), thus potentially restricting haloperidol action to one side of the BBB.